The impact of foreign trade on the Netherlands' real CO2 emissions - Bartosz Fortunśki (The Central European Review of Economics and Management (CEREM), 2019)
Aim: CO2 emissions and the related climate change are a global problem, where the direct impact of actions of individual countries depends on their total share in CO2 emissions. In order to assess the potential for policy measures, the openness of an economy, and the related import and export and their impacts on emissions should be considered. The aim of this paper is the attempt to show the real CO2 emissions of the Netherlands as well as the impact of its trade on CO2 emissions in other countries in the world and in the EU in 2015.Design / Research methods: This study was conducted on the group of countries that are the major emitters of CO2 in the world including most of the EU members. Countries with negligible CO2 emissions were omitted. Actual CO2 emissions were obtained by applying the actual emission factor. This takes into account the transfer of CO2 in export products and services as well as those imported by particular countries.Conclusions / findings: The real CO2 emissions in the Netherlands are significantly different from the gross values, which represent the CO2 emissions in the particular countries. It is also important to indicate that isolated actions of a single country within the European Union itself do not deliver the intended global and regional target - significant CO2 emissions reduction. The approach proposed in this study, when applied, may have serious implications for individual EU member states in implementing their energy policy objectives.Originality / value of the article: The article shows a different approach to the issue of CO2 emission, including the importance of international trade in a globalizing world.
Keywords: 330